Donor-specific cell-based assays in studying sensitivity to low-dose radiation: a population-based perspective - Dora eIl'yasova; Alexander eKinev; C. David Melton; Faith G Davis (Frontiers Media S.A., 2014)
Currently, a linear no-threshold model is used to estimate health risks associated with exposure to low-dose radiation, a prevalent exposure in the general population, because the direct estimation from epidemiological studies suffers from uncertainty. This model has been criticized based on unique biology of low-dose radiation. Whether the departure from linearity is toward increased or decreased risk is intensely debated. We present an approach based on individual radiosensitivity testing and discuss how individual radiosensitivity can be assessed with the goal to develop a quantifiable measure of cellular response that can be conducted via high-throughput population testing.